SISTEM PEMERINTAHAN NAGARI ( STUDI PADA NAGARI PADANG MAGEK KABUPATEN TANAH DATAR ) - Afdhal Prima; Zaili Rusli (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
Nagari Governance System (Study at Nagari Padang Magek Tanah Datar regency). The nagari governance system is a governance system that only legality in west Sumatra province. From the history, this governance system got many intervention from other governance system but nagari governance system keep defend it authenticity until now. According to that explanation, this study aims to determinate what is nagari governance system, how the implementation and what are the factors that can influence it by doing study in Nagari Padang Magek Kabupaten Tanah Datar. This research is qualitative research with descriptive method. The researcher trying to find the fact that appropriate with the truth. The data will be explains truly in order to get an understanding. The result of the research can be conclude that nagari governance system is a governance system which lead by a wali nagari who help by old customs and tradition institution, religion local institution, youth constitution, KAN, and BPRN. Nagari governance system in Padang Magek Tanah Datar regency base on conference and discussion with ideology, culture, and customs and tradition that keep defend until today.Key word : System, Governance, Nagari, Management, Niniak Mamak, Alim Ulama, Cadiak Pandai, KAN, BPRN